Kebutuhan dan Perilaku Pencarian Informasi Mahasiswa Uinsu - Franindya Purwaningtya; Dinda Rizki Anggurini Hasibuan; Eva Soraya; Hannum Anggininami; Imam Hardani Ritonga (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to analyze the information-seeking needs and behavior of UINSU students in the realm of libraries, to find out the pattern behind UINSU students in searching for library information, to find out the effects/responses that occur on UINSU students in seeking information. This research uses qualitative research with field research. Qualitative research is research that does not use calculations. This qualitative research on the meaning, reasoning, definition of certain situations (in certain contexts). The qualitative approach is more on the process than the end result. Therefore, the sequence of activities may change at any time, depending on the circumstances and the number of symptoms observed. This research results that UINSU students need information sources such as book research journals, resource persons, and also the internet in searching for information, and UINSU students will look for information in other university libraries, and Regional Libraries if the information needed cannot be found in the UINSU Library and visit the reading room and thesis room in search of information. Before searching for information, the informant will record what will find information so that it can be used and according to needs. Keywords: Needs, Behavior, Information Search